2007
DOI: 10.2146/ajhp070041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin E on cholesterol levels of hypercholesterolemic patients receiving statins

Abstract: Vitamin E supplementation did not affect total or low-density-lipoprotein cholesterol levels in hypercholesterolemic patients receiving lovastatin or simvastatin. A small but significant decrease in HDL cholesterol levels was observed in the group that received vitamin E supplementation during the supplementation period, but this decrease was no longer significantly different from the placebo group's levels two weeks postsupplementation. The decrease in HDL cholesterol levels did not appear to be related to ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 47 publications
0
15
1
1
Order By: Relevance
“…Similar to our study they didn’t find significant differences in any lipoprotein cholesterol fraction. However, unlike our study, a 6% decrease in HDL-C was detected within the vitamin E group (p < 0.05) (Leonard et al 2007). Following our study, LDL-C increased in all groups, but this increase was only significant in group E. This increase may be due to increasing the size of LDL-C or changing its fractions or by increase of its half life by decreasing LDL-C oxidation.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Similar to our study they didn’t find significant differences in any lipoprotein cholesterol fraction. However, unlike our study, a 6% decrease in HDL-C was detected within the vitamin E group (p < 0.05) (Leonard et al 2007). Following our study, LDL-C increased in all groups, but this increase was only significant in group E. This increase may be due to increasing the size of LDL-C or changing its fractions or by increase of its half life by decreasing LDL-C oxidation.…”
Section: Discussioncontrasting
confidence: 93%
“…In the present study, the number of platelet decreased nonsignificantly in groups P, C, and CE. Leonard and colleagues (2007) studied the effects of vitamin E (400 IU) on cholesterol levels of hypercholesterolemic patients receiving statins. Similar to our study they didn’t find significant differences in any lipoprotein cholesterol fraction.…”
Section: Discussionmentioning
confidence: 99%
“…5). Such mechanism could explain the inhibitory effect of tocopherols on blood HDL-cholesterol previously observed in human studies [45][46][47]. Moreover, in physiopathological state, such as insulin resistance and diabetes, where the intestinal cholesterol synthesis is increased [48], the effect of tocopherols could limit, at least in part, cholesterol overproduction.…”
Section: Discussionmentioning
confidence: 93%
“…Three studies to test this hypothesis in humans have not demonstrated decreased drug efficacy. When Leonard et al [45] gave vitamin E supplements to hypercholesterolemic patients, the supplements did not alter efficacy of either simvastatin or lovastatin, two drugs metabolized via a CYP3A-dependent mechanism. Werba et al [46] approached this problem by studying the effect of simvastatin (20 mg/day) or pravastatin 40 (mg/day) on α- and γ-tocopherol concentrations in hypercholesterolemic humans.…”
Section: Discussionmentioning
confidence: 99%